2017
DOI: 10.1007/978-3-319-69194-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Stem Cells and Their Microenvironment

Abstract: Glioblastoma (GBM) is the most common primary malignant astrocytoma associated with a poor patient survival. Apart from arising de novo, GBMs also occur due to progression of slower growing grade III astrocytomas. GBM is characterized by extensive hypoxia, angiogenesis, proliferation and invasion. Standard treatment options such as surgical resection, radiation therapy and chemotherapy have increased median patient survival to 14.6 months in adults but recurrent disease arising from treatment resistant cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 130 publications
0
38
0
1
Order By: Relevance
“…GSCs have been found to contribute to the recurrence and resistance to therapies in malignant gliomas (Kamiya-Matsuoka and Gilbert, 2015). Emerging evidence suggested that GSCs are able to self-renew and are refractory to cancer treatment (Sattiraju et al, 2017). Lee DH et al reported that the cardiac glycoside, digitoxin, was capable of inhibiting the neurosphere formation and decreased CD133 expression in human GCSs cells (Lee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…GSCs have been found to contribute to the recurrence and resistance to therapies in malignant gliomas (Kamiya-Matsuoka and Gilbert, 2015). Emerging evidence suggested that GSCs are able to self-renew and are refractory to cancer treatment (Sattiraju et al, 2017). Lee DH et al reported that the cardiac glycoside, digitoxin, was capable of inhibiting the neurosphere formation and decreased CD133 expression in human GCSs cells (Lee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…216,217 These cells interact with the surrounding microenvironment, regulating multiple signaling networks such as VEGF, NF-kB, EGFR, HIF1α, TGFβ, BMP, and NOTCH for promotion of tumor growth, metastasis and angiogenesis. 218 In contrast, GASC are nontumorigenic tumor supporting stem cells originated from mesenchymal stem cells mostly found in the perivascular area. GASCs are classified into two categories according to their marker profile and functions.…”
Section: Role Of Neurovascular Unit In Ischemia and Glioma Astrocytesmentioning
confidence: 99%
“…Stem cells have the capacity to self‐renew or differentiate into distinct cell populations . Mesenchymal stem cells have been identified in a variety of tissues, including the skin, where, by the formation of new cells, they guarantee the tissue repair after injuries.…”
Section: Perspectives/future Directionsmentioning
confidence: 99%